STUDY ON ESSENTIAL OIL COMPOSITION AND BIOLOGICAL ACTIVITIES OF ESSENTIAL OIL AND ETHANOL EXTRACT’S FROM ARTEMISIA SCOPARIA WALDST.et KIT GROWN IN MONGOLIA - Ayurzana, Amarjargal; Boldkhuu, Nandintsetseg; Shatar, Altantsetseg; Bayarhuu, Batbayar; Romanenko , Elena P.; Jambald, Irekhbayar (IJRDO-Journal of Applied Science, 2023)
Mongolia is rich in medicinal plants. Essential oils of aromatic and medicinal plants generally have a diverse range of activities because they possess many active constituents that work through a several modes of action. Artemisia, the largest genus of the family Asteraceae, has a number of effects against human and plant diseases [8].This study was aimed to evaluate antioxidant, cytotoxic activities of aerial parts ethanol extracts from Artemisia scoparia  Waldst.et Kit  grown in Mongolia. The antioxidant and cytotoxic activities of the essential oil and ethanol  extract was determined by using DPPH and MTT assays.  The ethanol extracts showed higher antioxidant activity than essential oil.  The essential oil of  Artemisia scoparia  Waldst.et Kit with a concentration of 150 mg/ml or 3μg/disk inhibits the growth of  S.enterica 10.6±0.58 mm, B.subtillus 11.6±1.15 mm, and has a moderate bacterial activity.The  half-lethal dose (IC50) 56.542 μg/ml  is  of essential oil of Artemisia scoparia Waldst. et. Kit, so essential oil of Artemisia scoparia  Waldst. et. Kit is active in inhibiting of liver cancer cell line  (HepG2).The half-lethal dose (IC50)  72.611 μg / ml   is  of essential oil  Artemisia scoparia Waldst. et. Kit,  which has the active  in  inhibiting the growth of human stomach  cancer  cell line (AGS).The results clearly showed that the essential oil presented satisfactory cytotoxic activity  against human stomach cancer cell line AGS. Our work revealed that the ethanol extracts and essential oil of Artemisia scoparia  Waldst.et Kit  grown in Mongolia has potential as sources of new antioxidant, and cytotoxic compounds, respectively.